Internalised stigma among psychiatric outpatients - Sapinoso, Rodhie D (My University, 2019)
Introduction: Self-stigmatisation is when an individual cognitively and emotionally internalises negative stereotypes, prejudice and discrimination. Previous studies have shown the severe impact of internalised stigma on multiple aspects of a patient’s well-being, from aggravating underlying psychiatric symptoms to severely decreasing quality of life. The aim of this study was to assess the presence and nature of self-stigma among outpatients attending psychiatric community clinics, comparing those with high levels of stigma to those with low levels in terms of demographics and clinical correlates. Methods: The study surveyed a sample of patients who attended the Sedibeng district psychiatric clinics between October and November 2016. Demographic and clinical details were obtained from consenting participants’ clinical records. The Internalised Stigma of Mental Illness (ISMI-29) questionnaire was administered by the principal investigator. An additional question was added to elucidate possible cultural or religious elements of self-stigma. Six generalised linear models were conducted to assess the influence of predictive factors on each dependent variable (i.e. alienation, stereotype endorsement, discrimination experience, social withdrawal, stigma resistance and total ISMI-29 score). Results: Of the 123 participants, 63.4% (n=78) demonstrated high levels of internalised stigma on total ISMI-29 score. The most reliable predictor of high stigma scores was number of psychiatric admissions (0.12+0.04, 2.62, 0.010). Having schizophrenia or bipolar disorder (0.12+0.04, 2.62, 0.010), belonging to a black ethnocultural group (-0.13+0.06, 2.13, 0.036), having comorbid substance use disorders or HIV (-0.05+0.02, 2.02, 0.045) and being single (0.15+0.06, 2.27, 0.026) were shown to elevate different subsets of the ISMI-29. Although 21,2% of the sample had cultural/religious attributions of mental illness, these were not shown to correlate with higher levels of self-stigma. Conclusions: Almost two-thirds of this sample of patients at the Sedibeng district psychiatry clinics experienced a high degree of internalised stigma, considerably higher than that reported in other settings (20-40%). A high level of internalised stigma was most reliably predicted by the number of psychiatric admissions
A research report submitted to the faculty of Health Sciences, University of the Witwatersrand in partial fulfillment of the requirements for the degree of the Masters of Science in Medicine in Psychiatry Johannesburg, 2019